Georgia's Path to Europe: A Corpus-Assisted Discourse Study of Presidential and Prime-Ministerial Speeches - Nino Guliashvili (European Scientific Journal, ESJ, 2025)
Social and political phenomena come into existence through a discursive dimension. The linguistic construction of reality is pervasive and plays a predetermining role in shaping social and political environment. The present study applies the framework of Corpus-Assisted Discourse Studies (CADS) to explore how Georgia’s two political figures – former President Salome Zourabichvili and former Prime Minister Irakli Garibashvili – discursively represent Georgia’s path toward European Union accession. The research examines 97 speeches (69 presidential/28 prime-ministerial) delivered between March 2022 and December 2023, totaling 64,321 and 29,559 tokens, respectively. Quantitative analyses were conducted using #LancsBox ® to identify keyword frequencies, collocates, and statistically significant differences, while Wmatrix5 ® was employed for semantic-domain and stance-related analysis. The findings reveal that both politicians tend to frame Georgia’s European trajectory through recurring metaphors of journey and family, yet their linguistic emphases diverge: Salome Zourabichvili’s discourse stresses European values, moral obligation, and collective unity, whereas the Prime Minister foregrounds national sovereignty, economic progress, and pragmatic governance. Despite differing communicative styles, both leaders converge in portraying EU integration as Georgia’s shared national destiny.